Climate smart cocoa value chains: Presentation at Journees Nationales du Cacao et du Chocolat - Abidjan, Ivory Coast - Bunn, Christian; Lundy, Mark M.; Castro, Fabio (2016)
What is the projected impact of climate change on cocoa value chains in Ivory Coast What can be done to improve the resilience of these production systems to the projected impact of climate change?